Using Military Build-Ups to Capture Fiscal Shocks: A Reassessment - Weonho Yang; Jan Fidrmuc; Sugata Ghosh (Center for Economic Studies and ifo Institute (CESifo), 2014)
Ramey (2011a) and others argue that increases in government spending associated with wars and military build-ups constitute a good instrument for measuring the macroeconomic effects of fiscal shocks. We argue that this instrument has two important drawbacks: the composition of government spending during military build-ups in the US differs substantially from general government expenditure, and increases in military spending tend to crowd out federal non-defense spending as well as spending by state and local governments. These weaknesses help to explain why fiscal multipliers estimated with military build-ups tend to be smaller than those estimated using other approaches.
Keywords: E13; E22; E62; 330; fiscal shocks; fiscal multiplier; military build-ups; US economy